Peculiarities of morphological indexes of the pushers of the nucleus at the stage of specialized basic preparation - Рожков, Владислав Олександрович (Slobozhanskyi Herald of Science and Sport, 2016)
Rozhkov V. Purpose: explore peculiarities morphological indexes of the pushers of the nucleus at the stage of specialized basic preparation. Material & Methods: the study was attended by 12 core pushers 15–17 years who were at the stage of specialized basic training. We used the following methods: analysis and synthesis of scientific and technical literature, the definition of anthropometric indicators index method. Results: presented morphological indexes of the pushers of the nucleus at the stage of specialized basic preparation. Conclusions: the figures obtained showed that at the stage of specialized basic preparation the somatotype of shot-putters corresponds the somatotype of the highly qualified shot-putters.